Sleep patterns among middle school students: a three-year longitudinal study in the context of China’s “Double Reduction” policy - Dai, Jiansong; Huang, Yan; Zhao, Yifan; Xu, Kai; Gu, Zhongke; Chen, Gangrui (Frontiers in Public Health, 2025)
ObjectiveThis longitudinal study aims to describe the sleep pattern trajectories among Chinese middle school students over a three-year period.MethodsFrom December 2021 to December 2023, 82 middle school students were monitored for 2 weeks per academic year for a period of 3 years using the Huawei Band 6 wearable devices, and sleep parameters were collected at each stage and statistically analyzed.ResultsFor 82 middle school students, their sleep onset time gradually delayed over the years, leading to a yearly decrease in night sleep duration (Grade 7: 452.3 ± 32.4 min; Grade 8: 432.9 ± 38.6 min; Grade 9: 420.4 ± 37.9 min, F = 50.30, p<0.001). The incidence of sleep deprivation gradually increased (x2 = 17.09, p = 0.0002). Over the 3 years, there were no statistically significant differences in wake-up time, sleep onset time, or night sleep duration between genders, and there was no interaction with time and gender. Sleep duration on rest days was significantly longer than on school days (p < 0.001). There was a significant interaction between time and time type (rest day/school day) on daytime sleep duration, wake-up time, and sleep onset time (p < 0.05).ConclusionThis study indicates that middle school students experience a gradual decrease in sleep duration over 3 years. Schools are advised to delay morning start times and enhance sleep hygiene education for students and parents as part of measures to address insufficient sleep among students.